PERLINDUNGAN HUKUM KONSUMEN TERHADAP PEREDARAN KOSMETIK PALSU BERDASARKAN UU NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN DAN PERATURAN BPOM NOMOR 23 TAHUN 2019 - Vera Wheny Setijawati Soemarwi; Yudith Ridzkia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2023)
In general, law is defined as a set of rules of conduct that regulates and coerces society. A country uses law in every step of the way. Therefore, the law becomes a benchmark for state institutions in carrying out all their affairs. The existence of the Consumer Protection Law is a legal product created by legislative institutions to ensure that the law protects as well as stipulates the rights and obligations of consumers and business actors. The problem that is currently being discussed is the distribution of dangerous counterfeit cosmetic products. This research uses a socio-legal studies approach in examining the behaviour of cosmetic business actors in e-commerce media. This research aims to analyze the consumer protection law due to the use of dangerous cosmetic products and the role of BPOM in the distribution of dangerous cosmetics in Indonesia. The results of this research show that consumer protection in the distribution of dangerous cosmetics is regulated in the Consumer Protection Law, Health Law, Minister of Health Regulation, BPOM Regulation, and related technical regulations.